The compliance of hypertension patients in taking medication at Sukasada II Primary Health care from January - March 2016 - Shobana Raveendran; Komang Ayu Kartika Sari (Intisari Sains Medis, 2018)
Background: Hypertension is a chronic disease where the adherence to therapy should be given serious attention. Compliance behavior is to obey the doctor's advice or procedure from the doctor about the use of drugs which had been prescribed by a consultation process between the patient and the patient's family physician. The health providers were influenced by two factors: behavioral and non-behavior factors which determined or shaped by three main factors such as predisposing factors, enabling factors, and reinforcing factors. The aim of this study to assess the compliances of taking medication in hypertensive patients at the Sukasada II Buleleng primary health care.Method: It was a quantitative descriptive study. The respondents were all hypertension patients who come to the Sukasada II primary health care from the period of January to March 2016. Data were obtained through interviews and questionnaires distributed to respondents who met the inclusion criteria and exclusion. The univariate and bivariate analysis was conducted in this study.Results: The results of the research show the number of 84 sample contained 1 subjects with good adherence, 14 subjects with moderate adherence, and 69 subjects with less adherence. The cross tabulation showed that poor medication adherence in the elderly (90.9%), followed by male gender (84.1%), low education (82.7%), higher knowledge (85.0%), perception at close distance (85.7%), travel time â‰¥ 15 minutes (86.0%), route conditions (84.1), do not have access difficulties (83.9), good family support (82.9), the low role of health care (100%), and did not have any comorbidities (83.1%).Conclusion: The trend of hypertensive patients that are not taking medication mostly come from submissive to men, senior citizens, low educational level, and lesser role of healthcare personnel.